Effect evaluation of agricultural water conservation policies in China - WANG Xiaoyan, WANG Taixiang, LIU Shuling (Ziyuan Kexue, 2024)
[Objective] The purpose of implementing active agricultural water conservation policies is to improve the utilization efficiency of water resources, alleviate the conflict between water resource supply and demand, and promote the sustainable development of agriculture. Correspondingly, active agricultural water conservation policies are an important way to achieve these goals. Exploring the effects of the policies is of great theoretical and practical significance for the scientific formulation and improvement of China’s agricultural water conservation policy. [Methods] Based on the agricultural water conservation policies promulgated by the Chinese government from 2011 to 2021, this study used the method of quantitative analysis of policy texts to measure the policy effectiveness in five dimensions: policy strength, objectives, measures, supervision, and feedback, and established a multiple regression model to assess the implementation effects of different policy tools. [Results] The results show that: (1) The overall effectiveness of the policies showed a fluctuating trend, but the average effectiveness of the policies in each year was generally low; (2) Among the five dimensions of policy effectiveness, there are many measures, but the intensity is low, the objectives are not specific enough, and the supervision and feedback are insufficient; (3) Among the policy tools, command-and-control and capacity-building policy tools had higher total and average effectiveness than economic-incentive and persuasive policy tools; (4) Each policy tool in the policy text had a lagged effect on the effective utilization coefficient of irrigation water, and the use of command-and-control and economic-incentive policy tools had a significant positive effect on the improvement of the effective utilization coefficient of irrigation water, while the role of persuasive and capacity-building policy tools needs to be further improved. [Conclusion] Therefore, first, China’s agricultural water conservation policies should be formulated in a way that strengthens top-level design and inter-sectoral coordination. Second, content effectiveness should be further improved and the specific content of the policy dimensions should be continuously enriched. Third, the four types of policy tools should be used in a synergistic manner to promote policies that produce good results.